Methylglyoxal evokes acute Ca2+ transients in distinct cell types and increases agonist-evoked Ca2+ entry in endothelial cells via CRAC channels. (March 2019) - Sachdeva, Robin; Fleming, Thomas; Schumacher, Dagmar; Homberg, Sarah; Stilz, Kathrin; Mohr, Franziska; Wagner, Andreas H.; Tsvilovskyy, Volodymyr; Mathar, Ilka; Freichel, Marc
Graphical abstract: Highlights: As in neurons, methylglyoxal (MG) evokes acute [Ca 2+ ]i elevations in mesangial cells. In endothelial cells (ECs) MG doesn't evoke any instantaneous changes in [Ca 2+ ]i . In ECs, chronic MG stimulation (300 μM, 6 h) facilitates agonist-induced Ca 2+ entry. Ang II-evoked Ca 2+ entry facilitated by MG is blunted by CRAC blocker GSK 7975A. Abstract: Methylglyoxal (MG) is a by-product of glucose metabolism and its accumulation has been linked to the development of diabetic complications such as retinopathy and nephropathy by affecting multiple signalling pathways. However, its influence on the intracellular Ca 2+ homeostasis and particularly Ca 2+ entry, which has been reported to be mediated via TRPA1 channels in DRG neurons, has not been studied in much detail in other cell types. In this study, we report the consequences of acute and long-term MG application on intracellular Ca 2+ levels in endothelial cells. We showed that acute MG application doesn't evoke any instantaneous changes in the intracellular Ca 2+ concentration in immortalized mouse cardiac endothelial cells (MCECs) and murine microvascular endothelial cells (muMECs). In contrast, an MG-induced rise in intracellular Ca 2+ level was observed in primary mouse mesangial cells within 30 s, indicating that the modulation of Ca 2+ homeostasis by MG is strictly cell type specific. The formation of the MG-derived advanced glycation end product (AGE) MG-H1 was found to be time and concentration-dependent in MCECs. Likewise, MG pre-incubation for 6 h increased the angiotensin II-evoked Ca 2+ entry in MCECs and muMECs which was abrogated by inhibition of Calcium release activated calcium (CRAC) channels with GSK-7975A, but unaffected by an inhibitor specific to TRPA1 channels. Quantitative PCR analysis revealed that MG pre-treatment did not affect expression of the genes encoding the angiotensin receptors AT1R (Agtr 1a & Agtr 1b), Trpa1 nor Orai1, Orai2, Orai3, Stim1, Stim2 and Saraf which operate as constituents or regulators of CRAC channels and store-operated Ca 2+ entry (SOCE) in other cell types. Together, our results show that long-term MG stimulation leads to the formation of glycation end products, which facilitates the agonist-evoked Ca 2+ entry in endothelial cells, and this could be a new pathway that might lead to MG-evoked vasoregression observed in diabetic vasculopathies.